792 OUTCOMES AFTER TOTALLY MINIMALLY INVASIVE VERSUS HYBRID OR OPEN IVOR LEWIS ESOPHAGECTOMY: RESULTS FROM THE INTERNATIONAL ESODATA STUDY GROUP. (17th September 2021) - Van Der Wilk, Berend; Hagens, Eliza R C; Eyck, Ben M; Gisbertz, Suzanne S; Hillegersberg, Richard; Nafteux, Philippe; Schröder, Wolfgang; Nilsson, Magnus; Wijnhoven, Bas P L; Lagarde, Sjoerd M; Berge Henegouwen, Mark I
Abstract: : To compare complications following totally minimally invasive (TMIE), laparoscopically assisted (hybrid) and open Ivor Lewis esophagectomy in patients with esophageal cancer. Three randomized trials have reported benefits for minimally invasive esophagectomy. Two studies compared TMIE versus open esophagectomy and another compared hybrid versus open Ivor Lewis esophagectomy. Only small retrospective studies compared TMIE with hybrid Ivor Lewis esophagectomy. Methods: Data were used from the International Esodata Study Group assessing patients undergoing TMIE, hybrid or open Ivor Lewis esophagectomy. Primary outcome was pneumonia, secondary outcomes included incidence and severity of anastomotic leakage, (major) complications, length of stay, escalation of care and 90-day mortality. Data were analyzed using multivariate multilevel models. Results: In total, 4733 patients were included in this study (TMIE:1472, hybrid:1364 and open:1897). Patients undergoing TMIE had lower incidence of pneumonia compared to hybrid (10.9% vs 16.3%, Odds Ratio (OR):0.56, 95%CI: 0.40–0.80) and open esophagectomy (10.9% vs 17.4%, OR:0.60, 95%CI: 0.42–0.84) and had shorter length of stay (median 10 days (IQR 8–16)) compared to hybrid (14 (11–19), p = 0.041) and open esophagectomy (11 (9–16), p = 0.027). Patients undergoing TMIE had higher rate of anastomotic leakage compared to hybrid (15.1% vs 10.7%, OR:1.47, 95%CI: 1.01–2.13) and open esophagectomy (7.3%, OR:1.73, 95%CI: 1.26–2.38). No differences were reported between hybrid and open esophagectomy. Conclusion: Compared to hybrid and open Ivor Lewis esophagectomy, TMIE resulted in a lower pneumonia rate, a shorter hospital length of stay but a higher anastomotic leakage rate. The impact of these individual complications on survival and long-term quality of life should be further investigated.